Examining the performance of software defined virtual local area network - Abubakar, Adamu; Ahmed, Mohamud Abdulkadir (Penerbit UTM Press, 2022)
For more than three decades, the Virtual Local Area Network (VLAN) has been one of the most popular systems virtualization groups of users on both local and corporate networks. Because of the advantages that VLAN provides, network managers and operators have continued to use it in the creation of their networks and have even extended its use to include cloud computing networking. Previous research studies have established a lot of issues associated with VLAN architecture. Typically, it was revealed that it is difficult to set up a complex VLAN, and even it is successful, it leads to computational time-consuming, and prone to error to process majority of complex VLAN. Considering this, the current research examines the performance of “Software Defined- VLAN”. This is because Software-Defined Network (SDN) is a viable alternative network architecture that allows the separation of information and control functions on devices. It appears to be a promising optimized option VLAN administration. The SDN-enabled VLAN testbed was set out and implemented using OpenFlow. SDN-Enabled VLAN and a conventional VLAN. The finding revealed that SDN-enabled VLAN offers higher network performance, lower packet transfer delay, and a more efficient configuration.